NRAS mutant melanoma arising in a giant congenital melanocytic nevus in an infant - Neha Bansal; Mou Das; Uttara Chatterjee; Mamata Guha Mallick; Neeraj Arora; Deepak K Mishra (Wolters Kluwer Medknow Publications, 2021)
Pediatric melanomas are uncommon and sometimes arise in the background of giant congenital melanocytic nevus (GCMN). A 1-year-old girl was born with GCMN affecting her left half of the face and smaller nodules affecting trunk, hands, and feet. She developed an ulcerated lesion on the left temporoparietal scalp. The lesion showed features of GCMN along with large nests of a tumor composed of round cells with a vesicular nucleus, prominent nucleolus, plentiful mitoses, and areas of necrosis. Immunostaining for desmin, LCA, CD 20, CD 34, CD 99, BCL-2, and FLI1 was negative. Tumor cells showed immunopositivity for S-100 and HMB-45 confirming the diagnosis of melanoma. Immunostaining for BRAF V600E was negative; however, NRAS mutation was detected on next-generation sequencing. Unlike adult melanomas BRAF mutations are rare but NRAS mutations have been reported in pediatric melanomas. Adjunctive molecular testing will be important to understand the genetic basis of this disease and future targeted therapy.